Experimental study on flexural behavior of full-scale retard-bonded prestressed UHPC variable section cantilever beams. (1st June 2023) - Xiong, Xueyu; He, Linyi; Bao, Lianjin
Highlights: The proposed variable section cantilever beam combined the UHPC with RBPT and adopted novel structural form. For the beam with variable section, it is necessary to determine the cracking and failure section firstly. The role of structural plates should be considered in the model due to the particularity of π-shaped section. The model proposed in this study can well estimate the flexural capacity of the UHPC beams than the existing design codes. Abstract: Ultra high performance concrete (UHPC) cantilever beams are firstly used as the main load-bearing components in an open-air spiral staircase of a grand opera house under construction. In order to achieve the requirements of light weight, long span, good durability and strong bearing capacity, UHPC and retard-bonded prestressed tendon (RPBT) are combined in the cantilever beam with π-shaped section that varies along the length of the beam. In order to study the flexural behavior of the cantilever beam and provide reference for the design, through the experiment on flexural behavior of two full-scale (15.04 m long) retard-bonded prestressed UHPC variable section cantilever beams, the failure phenomenon, crack distribution, stress development of UHPC and steel bars, and prestress increment were studied. The test results show that each variable section cracked in turn. The failure section is 2.6 m away from the beam root. After unloading, the deflection recovery (87.8 % of the maximum deformation) was obvious, the prestress did not fail. The beam had good bearing capacity and ductility. For the beam with variable sections, it is necessary to determine the cracking and failure section firstly. The calculation models of the cracking bending moment M cr and the ultimate bending moment M u are established, which are in good agreement with the experimental results. The role of structural plates should be considered in the model due to the particularity of π-shaped section. For further exploration, It is found that the restimate of the flexural capacity is related to the the ratio of compression zone height to section height x / h in the existing design codes. The smaller the x / h is, the flexural capacity will be underestimated. However, the proposed model can well estimate the flexural capacity, which is in better agreement with the existing experimental results than the design codes.